Making Value of Household Waste through Waste Bank - Dwi Atmanti, Hastarini; Wahyu Rejekiningsih, Tri (Lafadz Jaya Publisher, 2024)
This study examines the role of waste banks in enhancing the economic value of household waste while promoting environmental sustainability. Focusing on the waste bank implemented in Susukan Siroto, East Ungaran District, Semarang Regency, Indonesia, the research evaluates its impact on the community's waste management practices and economic potential. The descriptive qualitative method was employed, involving interviews with 30 participants from the Family Empowerment and Welfare Group. Findings reveal that waste banks effectively increase awareness about waste sorting and recycling. Through systematic waste management, including sorting and depositing waste, communities gained both financial benefits and environmental improvements. Data from two implementation phases (June and August 2024) show a significant increase in waste deposits and financial returns for participants. Inorganic waste, such as plastic bottles, used cooking oil, and boxes, were transformed into valuable commodities, demonstrating the circular economy concept. The study highlights the importance of community involvement and education in achieving sustainable waste management. Waste banks not only reduce waste volume at landfills but also contribute to economic resilience, environmental conservation, and social harmony. The findings suggest that waste banks serve as a practical model for waste valorization, aligning with sustainable development goals.